Supersymmetric Dyons, Superstrings, and Rotating Wormholes - E. Olszewski (Advances in High Energy Physics)
We construct supersymmetric dyon solutions based on the ‘t Hooft/Polyakov monopole. We show that these solutions satisfy κ-symmetry constraints and can therefore be generalized to supersymmetric solutions of type I SO32 string theory. After applying a T-duality transformation to these solutions, we obtain two D3-branes connected by a wormhole, embedded in an M5-brane. We analyze the geometries of each D3-brane for two cases: one corresponding to a dyon with vanishing spin and the other corresponding to a magnetic monopole with nonvanishing spin. In the case of the vanishing spin, the scalar curvature is finite everywhere. In the case of the nonvanishing spin, we find a frame dragging effect due to the spin. We also find that the scalar curvature diverges along the spin quantization axis as 1/ρ2, ρ being the cylindrical, radial coordinate defined with respect to the spin axis. These solutions demonstrate the subtle relationship between the Yang-Mills and gravitational interactions, i.e., gauge/gravity duality.